2021
DOI: 10.1053/j.jrn.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coffee Consumption on Renal Outcome: A Systematic Review and Meta-Analysis of Clinical Studies

Abstract: Objective: Drinking coffee is one of the most common daily habits, especially in the developed world. Along with caffeine, coffee has various ingredients that have been suggested to have beneficial effects, including antioxidant, antiinflammatory, anticarcinogenic, antithrombotic and antifibrotic effects. In this systematic review and meta-analysis, we investigated the relationship between coffee intake and chronic kidney disease (CKD) related outcomes.Design and Methods: Literature search was performed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…The present study may suggest that drinking coffee and tea beyond 0-40% fluid requirements is associated with higher eGFR. While this criterion is binary, the protective effects of coffee nonetheless appear to be dose-dependent (65). Given that the STANISLAS population displayed a normal eGFR on average, we were unable to focus on CKD per se, although it can be inferred from our results that participants who met the coffee and tea criteria may exhibit a better preserved kidney function.…”
Section: Hbi Components and Kidney Outcomesmentioning
confidence: 81%
“…The present study may suggest that drinking coffee and tea beyond 0-40% fluid requirements is associated with higher eGFR. While this criterion is binary, the protective effects of coffee nonetheless appear to be dose-dependent (65). Given that the STANISLAS population displayed a normal eGFR on average, we were unable to focus on CKD per se, although it can be inferred from our results that participants who met the coffee and tea criteria may exhibit a better preserved kidney function.…”
Section: Hbi Components and Kidney Outcomesmentioning
confidence: 81%
“…This study reported that GC did not decrease kidney function in obese rats. Coffee consumption reduces the risk of chronic kidney disease [36]. Another study also reported that GC extract therapy at a dose of 1000 mg/kg BW/day was not toxic to the liver and kidneys.…”
Section: Discussionmentioning
confidence: 94%
“…Shortly, higher dose and serum levels of lithium, longer cumulative duration of lithium use, and later onset of illness lead to impaired renal functions. Caffeine consumption, another predictor of CKD, was reported to be dose-dependently associated with lower CKD (Kanbay et al, 2021). It also seem important to assess the use of caffeine in lithium using patients.…”
Section: Discussionmentioning
confidence: 99%